INFLUENCE OF SPAN-UM PTKIN PUBLICATION STRATEGY ON BRAND AWARENESS: CASE STUDY ON NEW STUDENTS OF UIN SUNAN GUNUNG DJATI BANDUNG - Tedi Priatna; Muhammad Amar Khana (Jurnal Isema : Islamic Educational Management, 2025)
This study aims to examine the influence of the publication strategy of SPAN-UM PTKIN on the brand awareness of State Islamic Religious Universities (PTKIN) (Case Study on New Students of UIN Sunan Gunung Djati Bandung). This study uses a quantitative approach. The data collection technique involves preparing a pre-designed statement arrangement in the form of a questionnaire survey through Google Form using a five-point Likert scale. The population surveyed in this study consisted of all new students in the Class of 2025 at UIN Sunan Gunung Djati Bandung. Meanwhile, the sample in this study consisted of 318 people selected using a non-probabilistic technique. This study tested the hypothesis using the Partial Least Squares Structural Equation Modeling technique. The results of the study show that the publication strategy of SPAN-UM PTKIN affects PTKIN's brand awareness. The implications of this result are significant for institutions involved in implementing and promoting Islamic higher religious education in Indonesia. It underscores the importance of strengthening digital publications by the SPAN-UM PTKIN committee in collaboration with the university's public relations.